2002
DOI: 10.1152/ajpheart.01092.2001
|View full text |Cite
|
Sign up to set email alerts
|

Presence of cellular renin-angiotensin system in chromaffin cells of bovine adrenal medulla

Abstract: The presence of a local renin-angiotensin system has been established in organs that serve as angiotensin targets. In this study, the expression of angiotensinogen mRNA and subcellular localization of renin, angiotensin-converting enzyme, and angiotensin II were investigated in bovine adrenal medullary cells in primary culture. By light microscopy, expression of angiotensinogen mRNA, immunoreactive renin, angiotensin-converting enzyme, and angiotensin II were readily detectable only in the chromaffin cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…More recently, immunocytochemistry and subcellular fractionation analysis demonstrated that renin and Ang II partially colocalized in dense granules of adrenal chromaffin cells. ACE and AGT were also observed in Ang II-containing cells, suggesting intracellular synthesis of Ang II [69]. Expression and colocalization studies suggest involvement of renin and ACE in intracellular Ang II synthesis in the nervous system; however, these observations need to be confirmed using specific enzyme inhibitors.…”
Section: Intracellular Angiotensin II Synthesis In the Nervous Systemmentioning
confidence: 96%
“…More recently, immunocytochemistry and subcellular fractionation analysis demonstrated that renin and Ang II partially colocalized in dense granules of adrenal chromaffin cells. ACE and AGT were also observed in Ang II-containing cells, suggesting intracellular synthesis of Ang II [69]. Expression and colocalization studies suggest involvement of renin and ACE in intracellular Ang II synthesis in the nervous system; however, these observations need to be confirmed using specific enzyme inhibitors.…”
Section: Intracellular Angiotensin II Synthesis In the Nervous Systemmentioning
confidence: 96%
“…In VSMC, NO limits their proliferation and migration [64]. In addition to RAAS present in systemic circulation and its production in local tissues, there are also reports about the identification of an intracellular RAAS in certain cell types such as hepatoma cells [65], renal cortical cells [66], or adrenal medullary chromaffin and pituitary glandular cells [67]. Human and rat adrenal cortical cells stimulated with Ang II produce aldosterone via AT1R-upregulation of cytochrome P450 oxidase B2 and increased level of hydrogen peroxide, whereas pretreatment with losartan and antioxidants abrogates Ang II effects [68].…”
Section: Raas and Vascular Inflammationmentioning
confidence: 99%
“…Increasing evidence indicates that the adrenal medulla possesses an intrinsic renin‐angiotensin system. Recently, subcellular fractionation approaches and ultrastructural immunocytochemistry have demonstrated that renin, angiotensin‐converting enzyme, and angiotensin II are coexpressed in CV from cultured bovine chromaffin cells (Wang et al,2002). Moreover, angiotensinogen mRNA has been detected within the same cultured cells.…”
Section: Transmitter Peptidesmentioning
confidence: 99%
“…Moreover, angiotensinogen mRNA has been detected within the same cultured cells. In addition, angiotensin Type 1 and angiotensin II receptors have been documented on bovine chromaffin cells (Wang et al,2002). Angiotensin II has long been known as a stimulator of catecholamine release from adrenal chromaffin cells both in vivo and in vitro (Mazur‐Ruder et al,1979).…”
Section: Transmitter Peptidesmentioning
confidence: 99%